Manajemen Sumber Daya Manusia Dalam Mewujudkan Pembelajaran Berkualitas Di Pondok Pesantren Riyadlotuth Tholabah Buluspesantren Kebumen - Erni Fatmawati (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2023)
This research aims to describe the planning, organization, implementation and control of human resources in realizing quality learning at the Riyadlatuth Tholabah Bulus Pesantren Kebumen Islamic boarding school. The approach used in this research is descriptive qualitative. The research location is at the Riyadlatuth Tholabah Bulus Pesantren Kebumen Islamic boarding school. In this research, the research subjects were the boarding school leaders, lodge treasurers, lodge heads, deputy lodge heads, ustadz, infrastructure managers, lodge administrative staff, lodge secretaries, foundation chairs, foundation treasurers, and foundation supervisors. Furthermore, the informants for this research were students, guardians of students, community leaders, and Islamic boarding school committees. Research data was collected through in-depth interviews, participant observation, and document analysis. This research data was analyzed using interactive analysis techniques developed by Miles & Huberman, namely: data reduction, data presentation, and drawing conclusions. The results of the research show: (1) human resource planning in realizing quality learning at the Riyadlotuth Tholabah Bulus Pesantren Kebumen Islamic boarding school is carried out at the beginning of every year, always making a list of educators for the students; (2) organizing human resources in realizing quality learning at the Riyadlotuth Tholabah Bulus Pesantren Kebumen Islamic boarding school is carried out by holding meetings with educators, without any educational organization; (3) the implementation of human resources in realizing quality learning at the Riyadlotuth Tholabah Bulus Pesantren Kebumen Islamic boarding school has gone well because it is a routine; and (4) control of human resources in realizing quality learning at the Riyadlotuth Tholabah Bulus Pesantren Kebumen Islamic boarding school can be said to be quite good, control is also carried out by evaluating the human resources of the Islamic boarding school.